How to manage the infectious risk under anti-TNF in inflammatory bowel disease. - Culver, E; Travis, S (2010)
The advent of biological therapy has had a significant impact on the management of patients with inflammatory bowel disease. Nevertheless, anti-TNF-alpha agents are still used with caution, driven by concerns about the risk of infection. Stringent post-marketing surveillance programmes and registries have allowed early recognition of problems, highlighting an increased risk of infectious complications. Although the focus is on biological drugs, other immunomodulators have been less well scrutinised and similarly carry considerable risks of infection. It remains unclear whether the risk of infection from anti-TNF therapy is any different from conventional immunomodulators such as azathioprine or methotrexate, although it appears to be less than that ascribed to corticosteroids. The majority of patients on anti-TNF agents are on concomitant immunosuppressive medication, which makes ascribing risk to a specific drug more difficult. The risk of life-threatening opportunistic infections associated with anti-TNF therapy has obliged us to re-consider methods of prevention of infection and to develop guidelines for risk-stratification of patients with a diagnosis of inflammatory bowel disease. This encompasses vaccination and chemoprevention, appropriate treatment of underlying infection, patient education, travel advice and careful monitoring whilst on anti-TNF therapy. Contingency planning is essential. Implementing these preventative strategies will have an appreciable impact on the organisation of care and on current clinical practice.